Turkey and Iran Transcaucasia Policy: Comparative Analysis - А V Suleimanov (Vestnik RUDN. International Relations, 2010)
Turkey and Iran Transcaucasia modern foreign policy is analyzed. As is known, Turkey and Iran historically were the competing parties for spheres of influence in Transcaucasia, as well as Russia, the USA and the Great Britain. Regional relations between Azerbaijan, Armenia and Georgia are discussed in context of Nagorno-Karabakh and Georgia-South Ossetia conflicts and Caspian problem.